Multimodalizm w podróżach miejskich - rola projektów w jego wdrażaniu - Szołtysek, Jacek (Multimodality in City Travels - the Role of Projects in Implementing Them, 2008)
The paper deals with a new approach to city travel patterns and multimodality in city journeys. Based on theoretical approach the author shows the role of organizing and managing logistic projects and the necessity of preparing specialists for this kind of work in cities.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 190-198